A Requirement Model for Developing Staff Selection System (SSS) Toward Systematic Management for Human Resource Department at KUIN - Farahiza Zaihan, Azizan (2006)
The need for selection in hiring a new staff arises h m two facts. First, people differ in their characteristics and interest. Secondly, job is differs in the demands they make on workers. Selection is involves with systematically matching the right people to the right job. Selection is one of the main methods which an organization can use to ensure it has an effective work force. This project focuses on creating a requirement model for developing staff selection system for Kolej Universiti Insaniah (KUIN). The systematic process in hiring staff will assist KUIN to select appropriate people. Thus, it is hope that this requirement model will provide guidance and assistance for other researchers in designing systematic staff selection system (SSS) in the future.